Covid-19 Pandemic and Its Impact on Psychological Distress, Malignancy and Chronic Diseases: A Scoping Review - Hamza Khalifa Ibrahim; Noor-Alhooda Milood Al-Awkally; Abdul Samad; Hafeez ur Rehman Ali Khera; Waqar Zaib; Muhammad Hamza (Green Publisher Indonesia, 2022)
At the end of February 2020, the lifestyles of individuals all over the globe were drastically altered by the emergence of a new illness known as COVID-19. This study aims to analyze covid-19 pandemic and its impact on psychological distress, malignancy and chronic diseases. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library study) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of this study indicate that Covid-19 has a negative impact on the QOL of patients suffering from cancer, distress, and chronic illness. Furthermore, it exacerbates anaemia and fatigue in cancer patients, as well as hypertension or diabetes in cardiovascular patients.